The Relationship between Body Image Perception and Depression among Obstetric Fistula Patients - Anwar, Hira; Bukhari, Fatima Khurram (Annals of Human and Social Sciences, 2024)
This study investigated the relationship between depression levels and body image perception among obstetric fistula patients in South Punjab, Pakistan.Obstetric fistula, a result of prolonged and obstructed labor, significantly affects the psychological well-being of Pakistani women, especially those in rural areas with limited healthcare access. By using cross sectional design 223 women aged 18-35 from various South Punjab cities were recruited. Depression levels were assessed using the Patient Health Questionnaire (PHQ-9), and a researcher-developed Body Image Perception Scale evaluated body image perceptions.Significant correlations emerged among variables. Residence, socioeconomic status, and employment status correlated negatively with depression, while age correlated positively. Education level showed a paradoxical relationship with depression. Additionally, a significant negative correlation existed between depression and body image perceptions, indicating the impact of negative body image on depression levels. Targeted interventions and further research are crucial to address the mental health challenges faced by obstetric fistula patients in Pakistan, particularly in rural areas, emphasizing comprehensive support for affected women.